SOSIALISASI RANCANGAN PENERANGAN JALAN UMUM UNTUK ANTISIPASI TINDAKAN KRIMINAL DI DESA TUNTUNGAN I - Muhammad Rafly Prasetya; Tarigan, Amani Darma (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this service activity is to improve the comfort and safety of residents by designing and installing PJUs at several vulnerable points. The lack of public street lighting (PJU) in Tuntungan I Village, Pancur Batu District, Deli Serdang Regency, raises community concerns about the potential for criminal acts, especially at night. The methods used include direct surveys, field observations, and interviews with the local community to determine the needs and priority locations for street lighting installation. The results of the program showed an increase in the community's sense of security and active participation in supporting the sustainability of street lighting. The evaluation also recommends continued support from the local government so that the program can be expanded to all areas of the village.